1986
DOI: 10.1038/jcbfm.1986.11
|View full text |Cite
|
Sign up to set email alerts
|

Abstinence Improves Cerebral Perfusion and Brain Volume in Alcoholic Neurotoxicity without Wernicke-Korsakoff Syndrome

Abstract: Twenty severe chronic alcoholic patients with signs of neurotoxicity but without Wernicke-Korsakoff syndrome were treated by abstinence from alcohol and examined prospectively at intervals thereafter. Serial examinations included detailed medical histories, neurological examinations, cognitive capacity screening examinations, computed tomography scans with measurements of sulcal and ventricular volume, and measurements of regional CBF. All sedatives were withdrawn before CBF measurements were made. Before trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Numerous studies have illustrated that alcoholics exhibit cerebral hypoperfusion in the sober state both globally and regionally in the frontal, temporal, parietal, and occipital cortices as well as in the thalamus (Erbas et al, 1992;Kuruoglu et al, 1996;Melgaard et al, 1990;Mochizuki et al, 2001;Nicolás et al, 1993;Oishi et al, 1997;Oishi et al, 1999). The reduced CBF observed in alcoholism appears to be largely transitory and tends to normalize following sustained abstinence (Ishikawa et al, 1986), though the reported duration of abstinence associated with a return to normal perfusion has varied from as little as two months (Nicolás et al, 1993) to as long as four years (Gansler et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have illustrated that alcoholics exhibit cerebral hypoperfusion in the sober state both globally and regionally in the frontal, temporal, parietal, and occipital cortices as well as in the thalamus (Erbas et al, 1992;Kuruoglu et al, 1996;Melgaard et al, 1990;Mochizuki et al, 2001;Nicolás et al, 1993;Oishi et al, 1997;Oishi et al, 1999). The reduced CBF observed in alcoholism appears to be largely transitory and tends to normalize following sustained abstinence (Ishikawa et al, 1986), though the reported duration of abstinence associated with a return to normal perfusion has varied from as little as two months (Nicolás et al, 1993) to as long as four years (Gansler et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…For example, an investigation of the effects of abstaining from heavy cigarette smoking among elderly chronic smokers indicated subsequent improvements in CBF that continued to increase linearly for up to one year after cessation of smoking 16 . Other intervention studies have shown improved levels of cerebral perfusion and cognitive test scores following control of hypertension or smoking among patients with MID, 17–18 abstinence from excessive alcohol consumption among patients with alcoholic dementia, 19, 20 and following ventriculo‐peritoneal shunting of cerebrospinal fluid among patients with dementia secondary to normal pressure hydrocephalus 21 . Serial quantitative measurements of CBF and cognition provide sensitive and objective indicators of progression or remission of cerebral atherosclerosis, effective perfusion, and cerebral function compared with other clinical end‐points commonly used in trials of primary intervention, such as stroke and myocardial infarction 22–25 .…”
mentioning
confidence: 99%
“…Serial quantitative measurements of CBF and cognition provide sensitive and objective indicators of progression or remission of cerebral atherosclerosis, effective perfusion, and cerebral function compared with other clinical end‐points commonly used in trials of primary intervention, such as stroke and myocardial infarction 22–25 . For these reasons, smaller numbers of patients may provide statistically significant results 16–21 …”
mentioning
confidence: 99%
“…In a second study, this time of severe chronic alcoholics, these investigators found that global CBF improved between the first test after initial detoxification (postwithdrawal) and a retest 3-13 weeks into a period of continued abstinence. 80 In contrast to the first experiment, these results dem-onstrated the dramatic recovery in cerebral perfusion that can occur during abstinence. Together, this work indicates that alcohol-related changes in brain function are likely to exist in a sizable portion of the current population, and that these changes are clearly not limited to populations of alcoholics.…”
Section: Long-term Exposure To Alcoholmentioning
confidence: 68%